Comparative study of the effect of different exposure parameters of 635nm diode laser and toluidine blue O in eliminating Aggregatibacter actinomycetemcomitans biofilm from titanium implant surfaces - Mahnaz Arshad; Faraz Joshan; Nasim Chiniforush; Shima Afrasiabi (Photodiagnosis and Photodynamic Therapy)
Background: The aim of this study was to investigate the effects of antimicrobial photodynamic therapy (PDT) using 635 nm diode laser irradiation with an energy density of 6 to 30 J/cm2 and toluidine blue O (TBO) as a photosensitizer on the viability of Aggregatibacter actinomycetemcomitans attached to the surface of titanium implants. Materials and methods: Titanium implants contaminated with A. actinomycetemcomitans were treated with TBO alone or in combination with different exposure parameters (light doses of 6 - 30 J/cm2 at 635 nm) and 0.2 % chlorhexidine (CHX). After treatment, colony forming units (CFUs)/ml were determined to assess PDT efficacy. The structure of the biofilm of A. actinomycetemcomitans was analyzed by field emission scanning electron microscopy (FESEM). Results: Under optimal conditions, the colony count was reduced by ∼90 %. Treatment with CHX was somewhat more effective (colony formation was reduced by ∼95 %), but this agent has adverse effects that can be avoided with PDT. Conclusion: This study confirms the efficacy of PDT against A. actinomycetemcomitans depending on the light dose. Treatment with TBO + 635 nm diode laser has an effect that may be equivalent to that of CHX, but perhaps with fewer adverse effects.